(untitled) (Third Sector Social Economic Review, 2020)
Sport, especially football, which is one of the popular leisure activities of today, is a socialization tool that performs the function of transferring social values to individuals. It is important to examine the sociological aspect of football, which meets the individual’s need of having fun in every social class, as it is a mass entertainment tool. In this context, the subject of the study is to understand the causes of violent behavior during football competitions. In the study based on the qualitative method, it was found that there were 10 people who had prohibition from watching at least twice during the football matches in Bayburt, and 5 people who could be reached on a voluntary basis were applied semi-structured interview technique. During the interviews, it was found that individuals who went to football matches with fan groups received more positive reactions from their circles close to receiving punishment for violent behavior than individuals who went to the match individually. For this reason, it was found that “group dynamics” (fan group) is an important reason in understanding the causes of violent behavior in football. Another result of the study is that the punishment for violent behavior is considered as a deterrent by the participants.